The amplification effect of unreasonable human behaviours on natural disasters - Jie Fan; Baoyin Liu; Xiaodong Ming; Yong Sun; Lianjie Qin (Humanities & Social Sciences Communications, 2022)
Abstract Natural disasters occur when environmental systems have a disruptive effect on the socio-economic system. In recent years, particular unreasonable human behaviours have amplified losses from natural disasters as result of the increasing complexity of human systems. Because of the lack of both quantitative calculation of this amplification, and analysis of the root cause of these behaviours, existing risk assessment and management research rarely includes unreasonable human behaviour as a critical factor. This study therefore creates three simulation scenarios, each based on a twenty-first-century catastrophe in China, and calculates the disaster losses that are amplified when such behaviour increases exposure (the 2008 Wenchuan earthquake), vulnerability (the 2014 Ludian earthquake) and hazard (the 2021 Zhengzhou rainstorm) levels. In doing so, it intuitively demonstrates the amplification effect caused by unreasonable human behaviour. The results show that these behaviours amplified disaster losses significantly: increased exposure due to unscientific planning nearly doubled the death toll in the Wenchuan earthquake; high vulnerability caused by the low economic level of residents increased the disaster losses of the Ludian earthquake more than tenfold; and the elevated hazard intensity caused by anthropogenic climate change resulted in a 1.44-times expansion of the area severely affected by the Zhengzhou rainstorm. These behaviours have become an important cause of disasters, and the main driving factors behind them—such as neglecting disaster risk; the inability to cope with disasters; and a lack of certainty about how to deal with extreme events—are the inevitable outcomes of societal development. On this basis, we constructed an extended risk framework that included unreasonable behavioural factors and a disaster mechanism, to analyse in depth the relationship between human behaviours and disaster risk prevention in different developmental stages. The results provide an important reference for the development of risk management policies to control these unreasonable behaviours.